Homeopathy as an Adjuvant to Standard Care in Moderate and Severe Cases of COVID-19: A Single-Blind, Randomized, Placebo-Controlled Study - Kaur, Harleen; Kaushik, Subhash; Singh, Gurpreet; Kumar, Arvind; Singh, Shweta; Chatterjee, Tania; Ali, Syed; Gautam, Khushbu; Parewa, Maneet; Verma, Naval Kumar; Bhatnagar, Sushma; Singh, Suraj Pal; Shekhar, Varun; Khurana, Anil (Homeopathy, 2022)
Objectives This study aimed to evaluate whether individualized homeopathic medicines have a greater adjunctive effect than adjunctive placebos in the treatment of moderate and severe cases of coronavirus disease 2019 (COVID-19).Methods The study was a randomized, single-blind, prospective, placebo-controlled clinical trial set in the clinical context of standard care.Intervention Patients of either sex, admitted in a tertiary care hospital, suffering from moderate or severe COVID-19 and above 18 years of age were included. In total, 150 patients were recruited and then randomly divided into two groups to receive either individualized homeopathic medicines or placebos, in addition to the standard treatment of COVID-19.Outcome Measures The primary outcome was time taken to achieve RT-PCR-confirmed virus clearance for COVID-19. Secondary outcomes were changes in the Clinical Ordinal Outcomes Scale (COOS) of the World Health Organization, the patient-reported MYMOP2 scale, and several biochemical parameters. Parametric data were analyzed using unpaired t-test. Non-parametric data were analyzed using the Wilcoxon signed rank test. Categorical data were analyzed using Chi-square test.Results In total, 72 participants of the add-on homeopathy (AoH) group showed conversion of RT-PCR status to negative, in an average time of 7.53 ± 4.76 days (mean ± SD), as compared with 11.65 ± 9.54 days in the add-on placebo (AoP) group (p = 0.001). The mean COOS score decreased from 4.26 ± 0.44 to 3.64 ± 1.50 and from 4.3 ± 0.46 to 4.07 ± 1.8 in the AoH and AoP groups respectively (p = 0.130). The mortality rate for the AoH group was 9.7% compared with 17.3% in the AoP group. The MYMOP2 scores between the two groups differed significantly (p = 0.001), in favor of AoH. Inter-group differences in the pre- and post- mean values of C-reactive protein, fibrinogen, total leukocyte count, platelet count and alkaline phosphatase were each found to be statistically significant (p <0.05), favoring AoH; six other biochemical parameters showed no statistically significant differences.Conclusion The study suggests homeopathy may be an effective adjunct to standard care for treating moderate and severe COVID-19 patients. More rigorous, including double-blinded, studies should be performed to confirm or refute these initial findings.
Keywords: moderate to severe COVID-19; coronavirus infection; homeopathy; integrative care; pandemic; RT-PCR